Impact of Gatorade Beverage on Elite Female Badminton Players’ Performance - Sepideh Mehraein; Kaveh Khabiri; Mohammad Reza Pouria; Arash Rashidi; Majid Hajifaraji (Journal of Educational, Health and Community Psychology, 2017)
AbstractSports beverages assumed as one the principle factor on players' performance, and impact on their indicators, noticeably. Gatorade beverage is one of this primary beverages that in present study focused on its impact on elite female badminton players' performance in Iran. In the present survey has been considered in 2 groups of  Gatorade and control that included 79 participants. The data has been got based on 24 hours’ recall questionnaire on three different days in every week. As well, skin folds’ brachial triceps index was applied for body fat percent assessment. To quantity VO2max, Shuttle runs sub-maximal test was  used. Also, for controlling fluid intake in every two groups based on players’ body weight,150 ml per every 70 kg weight for every 15 minutes was recommended. Besides, for control of blood volume changes related to plasma blood glucose, hematocrit, hemoglobin, sodium, and potassium was measured during three time periods of zero, 30 minutes after the start and 90 minutes after the start. To end, to measure performance, standardized tests measure the indicators: aerobic power, speed, flexibilityy, agility, muscular strength, and endurance were used. The results showed that supply adequate water and fluids in during of sport, play a critical role in gaining the high level of female badminton players’ performance. In truth, the players who supply enough water shown better performance as compared with those who provide Gatorade beverage. Keywords: Badminton, Elite Female, Gatorade, Iran, Players, Sport Beverages.